Determining Key Influences on Patient Ability to Successfully Manage Noncommunicable Disease After Natural Disaster. Issue 3 (13th May 2019) - Ryan, Benjamin J.; Franklin, Richard C.; Burkle, Frederick M.; Smith, Erin C.; Aitken, Peter; Leggat, Peter A.
Abstract: Introduction: Natural disasters often damage or destroy the protective public health service infrastructure (PHI) required to maintain the health and well-being of people with noncommunicable diseases (NCDs). This interruption increases the risk of an acute exacerbation or complication, potentially leading to a worse long-term prognosis or even death. Disaster-related exacerbations of NCDs will continue, if not increase, due to an increasing prevalence and sustained rise in the frequency and intensity of disasters, along with rapid unsustainable urbanization in flood plains and storm-prone coastal zones. Despite this, the focus of disaster and health systems preparedness and response remains on communicable diseases, even when the actual risk of disease outbreaks post-disaster is low, particularly in developed countries. There is now an urgent need to expand preparedness and response beyond communicable diseases to include people with NCDs. Hypothesis/Problem: The developing evidence-base describing the risk of disaster-related exacerbation of NCDs does not incorporate the perspectives, concerns, and challenges of people actually living with the conditions. To help address this gap, this research explored the key influences on patient ability to successfully manage their NCD after a natural disaster. Methods: A survey of people with NCDs in Queensland, Australia collected data on demographics, disease, disaster experience, and primary concern post-disaster. Descriptive statistics and chi-square tests with a Bonferroni-adjustment were used to analyze data. Results: There were 118 responses to the survey. Key influences on the ability to self-manage post-disaster were access to medication, medical services, water, treatment and care, power, and food. Managing disease-specific symptoms associated with cardiovascular disease, diabetes, mental health, and respiratory diseases were primary concerns following a disaster. Stress and anxiety, loss of sleep, weakness or fatigue, and shortness of breath were common concerns for all patients with NCDs. Those dependent on care from others were most worried about shortness of breath and slow healing sores. Accessing medication and medical services were priorities for all patients post-disaster. Conclusion: The key influences on successful self-management post-disaster for people with NCDs must be reflected in disaster plans and strategies. Achieving this will reduce exacerbations or complications of disease and decrease demand for emergency health care post-disaster.